DIOCTOPHYMA RENALE (GOEZE, 1782) COLLET- MEYGRET, 1802 (DIOCTOPHYMATIDAE) IN GALICTIS CUJA (MOLINA, 1782) (MUSTELIDAE) IN RIO GRANDE DO SUL, BRAZIL - Cheuiche Pesenti, Tatiana (2012)
The objective of the study was to record the occurrence of Dioctophyma renale (Goeze, 1782) Collet- Meygret, 1802 in Galictis cuja Molina, 1782 in southern Brazil. Three specimens of G. cuja were found dead by running over on highways in the city of Pelotas, Rio Grande do Sul, Brazil and sent to the Laboratory of Parasitology of Wild Animals of the Federal University of Pelotas. Helminths were collected from the kidneys and the abdominal cavity with a mean intensity of infection of 4.66 helminths / host. In Brazil, D. renale had been reported parasitizing G. cuja only in the state of Paraná. Dioctophyma renale is reported for the first time in G. cuja in the state of Rio Grande do Sul, Brazil.